Report of the Working Group on Employment and Manpower - Planning Commission (Planning Commission, 1974)
Attempts were made from time to time to measure the incidence of the unemployment problem through the rural and urban labour force surveys by the National Sample Survey Organisation (NSSO) and special segmented studies conducted in respect of educated manpower, engineering graduates, matriculates etc. The Fourth Plan document did not make an estimate of the backlog of unemployment or employment potentials of plan investments as was the want in the earlier Plan documents.
Planning Commission
Planning Commission